Peningkatan Kualitas Pembelajaran IPA Melalui Pendekatan Inkuiri dengan Media Video Pada Peserta Didik Kelas III SDN 111/IX Desa Muhajirin - Ely Mawarni (Universitas Batanghari Jambi, 2020)
The problems that occur teachers do not apply varied learning and less developed methods. The teacher always views that learning must memorize, always read books, and work on problems. As a result, students feel bored, and less enthusiastic, shown by low student learning outcomes. The purpose of this study was to improve the quality of science learning which includes teacher skills, student activities, and student learning outcomes in grade III students of SDN 111 / IX Muhajirin Village. The design of this research is classroom action research with the stages of planning, implementing the action (applying the inquiry approach with video media), observing and reflecting. This research was conducted in 2 cycles, each cycle consisting of 2 meetings and carried out in 4 stages. This research was conducted at SDN 111 / IX Muhajirin Village, with the subject of this study being the teacher (researcher) and 34 students. In data collection, the techniques used are tests, observation, and documentation. The data analysis technique used was quantitative and qualitative data. The results of this study: (1) The teacher's skills in the first cycle obtained a total score of 13 in the sufficient category, and in the second cycle the score increased to 29 in the very good category. (2) The activity of students in the first cycle the average score for the activity of students was 22.3 in the good category, in the second cycle the average score for the activity of students increased to 28.5 in the very good category. (3) The learning outcomes of students in cycle I classical completeness reached 59% (20 of 34 students) with an average class score of 72.27 and in cycle II increased to 88% (30 of 34 students) with an average grade -averaged 84.23. The use of an inquiry approach using video media in science learning can improve teacher skills, student activities, and learning outcomes in class III students of SDN 111 / IX Muhajirin Village. The inquiry approach using video media improves the quality of learning so it is suggested that it can be applied to other learning.